Psychiatric Etiologies and Approaches in Altered Mental Status Presentations: Insights from Consultation Liaison Psychiatry - Hamm, Brandon; Rosenthal, Lisa J. (Seminars in Neurology, 2024)
Consultation liaison psychiatrists are frequently asked to evaluate patients with altered mental status (AMS). Psychiatrists have unique perspectives and approaches to care for confused patients, particularly optimizing facilitation of care and maintaining vigilance for diagnostic overshadowing. Psychiatrists also offer expertise in primary psychiatric illnesses that can overlap with AMS, and the most common etiology of AMS is delirium. In this article, we provide a consultation liaison psychiatrist perspective on AMS and related psychiatric conditions in addition to delirium. Manic and psychotic episodes have primary and secondary etiologies, with some symptoms that can overlap with delirium. Catatonia, neuroleptic malignant syndrome, and serotonin syndrome are potentially fatal emergencies, and require prompt index of suspicion to optimize clinical outcomes. Trauma sequelae, functional neurologic disorders, and dissociative disorders can present as puzzling cases that require psychiatric facilitation of care. Additionally, AMS is sometimes due to substance intoxication and withdrawal in the hospital. A nonstigmatizing approach to evaluation and management of delirium and AMS can ensure optimal patient care experiences and outcomes.
Keywords: altered mental status; delirium; consultation liaison psychiatry; catatonia; secondary psychosis; secondary mania; dissociation